Assessment of functional status through self-reported physical disability and performance-based functional limitations among elderly - Murat, Faizal; Ibrahim, Zuriati; Chan, Yoke Mun; Adznam, Siti Nur ‘Asyura (Invention Journals, 2017)
This cross-sectional study was conducted to assess functional status (self-reported physical disability and performance-based functional limitations) among community-dwelling elderly in Mukim Batu (Gombak), Selangor. A total of 258 subjects (males=123; females=135), aged 60 years and above were recruited. Physical disability was assessed by using a self-reported Instrumental Activities of Daily Living (IADL) instrument, whereas functional limitations were assessed through performance-based in terms of cognitive functioning, mobility status, manual dexterity and muscle strength by using Elderly Cognitive Assessment Questionnaire (ECAQ), Elderly Mobility Scale (EMS), lock and key test and handgrip strength respectively. The prevalence of self-reported physical disability was 58.1% (IADL≤7), with twice higher among older age group (≥75 years) as compared to younger age group (60-74 years) in both gender (p<0.05). As for performance-based, the prevalence of cognitive impairment (ECAQ≤5), mobility dependent (EMS≤13) and poor manual dexterity (lock and key test score≤2) was only less than 5% each. Similarly, older age group was liable to suffer from functional limitations as compared to the younger age group in both gender (p<0.05). Although females reported to have poorer performance-based than males, only cognitive functioning and handgrip strength were found to be significantly different between gender (p<0.05). In conclusion, self-reported physical disability indicated a higher prevalence of poor functional status than performance-based functional limitation. Thus, it is suggested to combine both method to give better information regarding overall functional status among elderly population.